(untitled) (Quinto Sol, 2020)
Statistics and Peronism are in a combinatory way a key point to observe the technical autonomy from both state and politics as an explanatory variable, so it is possible to understand official´s political actions. The 50th anniversary of the creation of the National Institute of Statistics and Census (1968-2018) is a first-rate chance of rethinking the ways in which official data have contributed to the conformation of national state in Argentina during the 20th Century. Hence, this paper reconstructs the case of a centralised statistical bureaucracy that produced the necessary information to make a planning for the “Nueva Argentina.” Thus, this presents the both bureaucratic and institutional trajectories of three government agents who managed national census bodies: Accountant Juan Miguel Vaccaro (1944-1945), Engineer Enrique Catarineu Grau (1946-1949) and Lawyer José María Rivera (1950-1955). The paper wants to study three different management styles as a way of thinking statistical agencies in Argentina, between 1944 and 1955, analysing the relationships between specialised bureaucracy and their military and political mentors.